2011
DOI: 10.53393/rial.2011.v70.32523
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento de micobactérias provenientes de amostras clínicas da região de Rio Claro: análise da frequência

Ariane Christine Degasperi Bertoletti,
Kaizer José Ferreira Alves,
Erica Chimara
et al.

Abstract: Os agentes etiológicos da tuberculose pertencem ao Complexo Mycobacterium tuberculosis (MT), porém outras espécies do gênero e de importância médica, denominadas micobactérias não causadoras de tuberculose (MNT), são frequentemente isoladas. A identificação correta e rápida das MNT é obrigatória para o diagnóstico, auxiliando o clínico na conduta terapêutica. A frequência da MT e MNT foi avaliada no período de 2003 a 2009, analisando-se 6.460 amostras clínicas, sendo 5.696 (88,2%) culturas negativas para micob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this study, the most frequently identified NTM from cultures with a negative result for MTBC on GenoType MTBDRplus were the potentially pathogenic M. fortuitum, MABC, MAC, M. kansasii and M. peregrinum. Bertoletti et al [18] analysed the frequency of NTM isolated from clinical specimens in Rio Claro, state of São Paulo. They found that the most prevalent NTM species were M. fortuitum, MAC, M. kansasii and MABC, the same species that were found with high prevalence in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the most frequently identified NTM from cultures with a negative result for MTBC on GenoType MTBDRplus were the potentially pathogenic M. fortuitum, MABC, MAC, M. kansasii and M. peregrinum. Bertoletti et al [18] analysed the frequency of NTM isolated from clinical specimens in Rio Claro, state of São Paulo. They found that the most prevalent NTM species were M. fortuitum, MAC, M. kansasii and MABC, the same species that were found with high prevalence in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Bertoletti et al . [18] analysed the frequency of NTM isolated from clinical specimens in Rio Claro, state of São Paulo. They found that the most prevalent NTM species were M. fortuitum, MAC , M. kansasii and MABC, the same species that were found with high prevalence in this study.…”
Section: Discussionmentioning
confidence: 99%